Perilaku Warga Peduli AIDS terhadap Penanggulangan HIV dan AIDS Di Kota Kupang - Wenzel Fernandez; Imelda February Ester Manurung; Sarcy M Toy; Honey I Ndoen (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2019)
The AIDS Tackling Committee (KPA) of KupangCity has been running several programs handling over the AIDS and HIV. One of the program is involving ordinary member of the society through AIDS Care Community Member. This research aim is to describe knowledge, attitude, and behavior of AIDS Care Community Members towards HIV and AIDS Tackling Program. This research is a survey, descriptive in nature. It was held from October 2017 to March 2018. The research population is 625. By using Slovin formula and simple random sampling technique, the sample is 93. The research results are as follows: the majority of the community member possessed a good knowledge (74%), all of the community members (100%) showed a positive attitude on the effort and 60,2% of the members of the community have conducted supportive acts towards the effort. Therefore, it is suggested that, there should be some upgrading’s on cadres capacity, especially their active involvement in mobilizing the society to conduct some supportive acts. Finally, it is expected that the overall society participation in tackling HIV and AIDS should be uplifted.